Neutrophils develop rapid proinflammatory response after engulfing Hb-activated platelets under intravascular hemolysis. (27th May 2019) - Bhasym, A; Annarapu, GK; Saha, S; Shrimali, N; Gupta, S; Seth, T; Guchhait, P
Summary: Neutrophils maintain immune homeostasis by engulfing apoptotic cells and debris. We describe the rapid activation of neutrophils after engulfing hemoglobin (Hb)-activated platelets, which are abundant in the circulation of hemolytic patients. Neutrophils from healthy individuals after engulfing Hb-activated platelets express elevated CD11b and secrete significant amounts of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, myeloperoxidase (MPO) and elastase within 4-h platelets, but not with free-Hb only in vitro . These neutrophils exhibit early onset of apoptosis and cell death after engulfing Hb-activated platelets, but not with free-Hb only. Further, our data from mice with phenylhydrazine-induced intravascular hemolysis display a gradual decrease in total neutrophil count, but the number of activated neutrophils and neutrophil–platelet aggregates increases, along with the rise of TNF-α, IL-1β, IL-6 and MPO in circulation. Our data from paroxysmal nocturnal hemoglobinuria (PNH) patients confirmed the observation of decreased total neutrophil counts, but elevated numbers of activated neutrophils, including neutrophil–platelet aggregates, in parallel with elevated expression of TNFA, IL1B and IL6 genes in neutrophils, also increased levels of these cytokines along with MPO in circulation, and this correlated directly with elevated intravascular hemolysis (high free-Hb in plasma). The patients' neutrophils displayed significant localization of intracellular Hb and platelets, unlike the counterparts from healthy individuals. Together, therefore, our observations suggest that Hb-activated platelets, which are abundant in the circulation of patients with hemolytic disorders, including PNH, promotes early onset of neutrophil activation and increases their proinflammatory response and leads to early apoptosis and cell death. Graphical Abstract: